CD4+CD25hiCD127− Treg and CD4+CD45R0+CD49b+LAG3+ Tr1 cells in bone marrow and peripheral blood samples from children with neuroblastoma. (1st December 2016) - Morandi, Fabio; Pozzi, Sarah; Barco, Sebastiano; Cangemi, Giuliana; Amoroso, Loredana; Carlini, Barbara; Pistoia, Vito; Corrias, Maria Valeria
ABSTRACT: Metastatic spread in the bone marrow (BM) at diagnosis is the worst prognostic factor for neuroblastoma (NB) patients. Here, we analyzed the presence of two immunosuppressive cell subsets, CD4 + CD25 hi CD127 − regulatory T (Treg) cells and CD4 + CD45R0 + CD49b + LAG3 + type 1 regulatory (Tr1) cells, in BM and peripheral blood (PB) samples from NB patients and controls. Frequency of both regulatory cell subsets was lower in BM and PB samples from NB patients than in respective healthy controls. No correlation was found between the frequency of Treg and Tr1 cells and prognostic factors at diagnosis, such as age and stage. Only MYCN amplification correlated to a higher number of Treg in BM and of Tr1 in PB. These findings suggested an altered trafficking of regulatory T cells in NB, but delineated a limited role of these subsets in BM microenvironment and/or periphery in NB. These observations should be considered designing immunotherapeutic approaches for metastatic NB.